Diseño de estrategias para la venta de nuevos productos en la Cooperativa Chibuleo agencia Latacunga. - Toaquiza Vega, Elsa Piedad (2022)
In this project, direct or personalized marketing strategies were designed for the sale of products to existing customers of the cooperative. For this, 3 databases were analyzed through the application of Big Data and relational databases. From there, the active clients were determined or extracted, with a total of 5,073. With this, five groups of clients were defined by their personal characteristics, which were Saver, Lonely, Lonely with credits, VIP and Sectorized. The first group is characterized by having only one savings account. The second, only has a current credit. The third has a savings account and a loan. The fourth handles credits above USD3,000 and arrears of less than 5 days, and the last group divides people by the geographical area in which they live in order to use geographical characteristics as an indicator of the type of strategies that could be used. generate. In this sense, a maximum of six strategies were designed for each type of client, having a total of 18 strategies, which are expected to generate an increase in profitability for the company in the coming year.